The significance of the academic word list among ESL tertiary students in a Malaysian public university - Lee, Bee Choo; Tan Ai Lin, Debbita Ai Lin; Manjet Kaur Mehar Singh,; Malini Ganapathy, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The Academic Word List (AWL) was compiled by Coxhead (2000) and consists of 570 word families. Along with 2,000 of the most common English words, knowledge of the words represented in this list is vital for the overall academic performance of students. It is widely acknowledged that the most acute linguistic need for students is vocabulary, followed by knowledge of subject matter and knowledge of syntactic structures. The current study adopted the survey approach and utilised an online questionnaire, which comprised of closed and open-ended items, specifically designed by the researchers. This paper examines the attitudes of Malaysian tertiary students towards the AWL for reading, writing, speaking and listening. The study involved the participation of 195 undergraduates comprising of Malays, Chinese and Indians who are enrolled in a Malaysian public university. Data was collected using a questionnaire designed by the researchers. The instrument was tested for reliability, with returned values indicating high reliability. It is found that the participants regard the knowledge of the words represented in the AWL as essential for academic reading and comprehension, writing, presentations, and understanding. Although generally assumed to be of significance to students, the effective implementation of a programme that accords specific attention to the AWL is still strongly reliant on the discernments of those who stand to benefit the most from it. The findings of this study are of significance to researchers, ESL/EFL teachers and learners, and course designers when developing AWL.